The Electrostatic Attraction and Catalytic Effect Enabled by Ionic–Covalent Organic Nanosheets on MXene for Separator Modification of Lithium–Sulfur Batteries. Issue 17 (18th March 2021) - Li, Pengyue; Lv, Haowei; Li, Zhonglin; Meng, Xueping; Lin, Zhang; Wang, Ruihu; Li, Xiaoju
Abstract: It is of great significance to mediate the redox kinetics and shuttle effect of polysulfides in pursuit of high‐energy‐density and long‐life lithium–sulfur (Li–S) batteries. Herein, a new strategy is proposed based on the electrostatic attraction and catalytic effect of polysulfides for the modification of the polypropylene (PP) separator. Guanidinium‐based ionic–covalent organic nanosheets (iCON) on the surface of Ti3 C2 is presented as a coating layer for the PP separator. The synergetic effects of Ti3 C2 and iCON provide new platforms to suppress the shuttle effect of polysulfides, expedite the redox kinetics of sulfur species, and promote efficient conversion of the intercepted polysulfides. The functional separator endows carbon nanotube/sulfur cathodes with excellent electrochemical performance. The average capacity decay per cycle within 2000 cycles at 2 C is as low as 0.006%. The separator is even effective in the case of sulfur content of 90 wt% and sulfur loading of 7.6 mg cm −2 ; the reversible capacity, areal capacity, and volumetric capacity at 0.1 C are as high as 1186 mA h g −1, 9.01 mA h cm −2, and 1201 mA h cm −3, respectively. This work provides a promising approach toward separator modification for the development of high‐performance Li–S batteries. Abstract : Modification of the separator of lithium–sulfur batteries, based on the electrostatic attraction and catalytic effect of polysulfides is presented by way of guanidinium‐based ionic–covalent organic nanosheets on the surface of conductive Ti3 C2 . The modified separator endows carbon nanotube/sulfur electrodes with significantly enhanced reversible capacity, areal capacity, volumetric capacity, and cycling stability.